The Influence of Achievement Motivation on Work Commitment - Utama, Hendri Budi; Luthfiani, Luthfiani; Kristiawan, Muhammad (Graduate Program Magister Manajemen Pendidikan, 2023)
There are still many teachers who carry out learning as a routine and formality only. The purpose of this study was to determine the influence of achievement motivation on work commitment at SMK Muhammadiyah 1 Padang. This research uses a quantitative approach with descriptive methods. The research sample consisted of 30 teachers, and the sample was determined randomly (simple random sampling). Data collection uses a questionnaire to measure work commitment variables and achievement motivation. The questionnaire provided a statement with alternative answers; always, often, sometimes, and never. The measurement scale uses a Likert scale. Quantitative data analysis techniques using statistics with the help of the SPSS program and Microsoft Office Excel. The research findings show that achievement motivation makes a significant contribution to teacher work commitment at SMK Muhammadiyah 1 Padang by 46.6%. This means that the higher the achievement motivation, the higher the teacher's work commitment. Conversely, the lower the achievement motivation, the lower the work commitment. To achieve teacher work commitment, it can be done by trying to increase achievement motivation for teachers.